Pengaruh Bermain Konstruksi (Lego) Terhadap Perkembangan Motorik Halus Pada Anak Pra Sekolah Di TK Miftahul Az-Zahra Desa Cihea Tahun 2022 - Rika Nur Zaqiah; Weslei Daeli; Risky Kusuma (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
fine motoric development is the development of motion that includes small muscles with eye-hand coordination. Fine motor development in children is related to the movement of the body, namely, muscles, nerves, and the brain each have a very important role. To determine the relationship between the intensity of social media use with the tendency to nomophobia. This study is a type of quasy experiment with a pretest-postest quasy experiment research design with a sample of 16 respondents. Based on the results of research that has been done that the influence of lego game intervention on the development of fine motoric TK Miftahul Az-zahra desa cihea. In addition, how to give lego games for 4 days with a duration of 30 minutes. Statistical test results based on the results of collecting data on fine motoric development are summed into a MAP (Mean Arterial Preasure) so that it can be concluded a significant effect on the provision of intervention lego games with p-value 0.000 which means p-value <0.05, therefore Ho rejected and Ha accepted that there is an effect of giving lego games on fine motoric development of children in kindergarten Miftahul Az-zahra cihea village. From this study shows the effect of lego play treatment to increase fine motoric development in preschool children P-Value = 0.000 t test. Which means that Ho is rejected and the sample supports the existence of a meaningful influence.